A Rare Case of Langerhans Cell Histiocytosis With Solitary Hepatic Involvement in an Adult Patient: Challenging Diagnosis, Transplantation, and Recurrence. (21st September 2018) - Rush, Natalia; Saxena, Romil; Lin, Jingmei
Abstract: Langerhans cell histiocytosis (LCH) rarely involves liver without systemic manifestation, especially in an adult population. We describe a case of LCH with solitary hepatic involvement that was initially diagnosed as antimitochondrial antibody (AMA)–negative primary biliary cholangitis (PBC), requiring transplantation. When disease recurred, the allograft was lost and the patient required a second transplantation. We have reviewed histopathologic material from both native and allograft specimens, including all biopsies and explant hepatectomies, and clinical data accumulated over a 10-year interval. A 46-year-old woman with a clinical history of panhypopituitarism presented with jaundice and pruritus. An initial hepatology workup including liver biopsy led to diagnosis of AMA-negative PBC with advanced fibrosis. Within a year, the patient progressed to decompensated cirrhosis requiring transplantation. Her posttransplantation course was complicated by frequent bouts of markedly elevated alkaline phosphatase (>1, 000 mg/dL) and gamma-glutamyl transferase with transaminases elevated above 100 mg/dL. These abnormalities, together with the liver biopsy findings of bile duct injury and portal eosinophilic infiltrate, were thought to be episodes of acute cellular rejection that occurred frequently during the first 2 years after transplantation. Her liver enzymes would show some improvement without complete normalization on high-dose steroid therapy and become elevated once the therapy stopped. Three years after transplantation, the diagnosis of LCH was established, and 4 years later, the patient lost the liver graft. The explanted allograft revealed patchy distribution of disease, confirming difficulty of LCH diagnosis on a core biopsy. A gold standard for LCH diagnosis relies on morphological and immunohistochemical examination. Establishing a diagnosis of LCH in the liver without systemic involvement is challenging due to the patchy nature of the disease and nonspecific inflammatory infiltrate with eosinophils that can mimic PBC and acute cellular rejection. Awareness of morphological features is crucial for pathologists to render the diagnosis when liver presents as solitary involvement.